Sex Difference in MasR Expression and Functions in the Renal System - Choopani, Samira; Nematbakhsh, Mehdi (Journal of the Renin-Angiotensin-Aldosterone System, 2022)
Renin-angiotensin system (RAS), as a critical system for controlling body fluid and hemostasis, contains peptides and receptors, including angiotensin 1-7 (Ang 1-7) and Mas receptor (MasR). Ang 1-7 implements its function via MasR. Ang II is another peptide in RAS that performs its actions via two Ang II type 1 and 2 receptors (AT1R and AT2R). The functions of AT2R and MasR are very similar, and both have a vasodilation effect, while AT1R has a vasoconstriction role. MasR affects many mechanisms in the brain, heart, blood vessels, kidney, lung, endocrine, reproductive, skeletal muscle, and liver and probably acts like a paracrine hormone in these organs. The effect of Ang 1-7 in the kidney is complex according to the hydroelectrolyte status, the renal sympathetic nervous system, and the activity level of the RAS. The MasR expression and function seem more complex than Ang II receptors and have interacted with Ang II receptors and many other factors, including sex hormones. Also, pathological conditions including hypertension, diabetes, and ischemia-reperfusion could change MasR expression and function. In this review, we consider the role of sex differences in MasR expression and functions in the renal system under physiological and pathological conditions.